Evaluation of myocardial work in patients with hypertrophic cardiomyopathy and hypertensive left ventricular hypertrophy based on non-invasive pressure-strain loops - Zhao, Qingqing; Cui, Cunying; Li, Yanan; Liu, Yuanyuan; Huang, Danqing; Wang, Ying; Hu, Yanbin; Liu, Ruijie; Zhu, Huizhen; Liu, Lin (Frontiers in Cardiovascular Medicine, 2022)
Background: The capacity to distinguish hypertrophic cardiomyopathy (HCM) from hypertensive left ventricular hypertrophy (H-LVH) based on morphological features obtained by conventional echocardiography is limited. We investigated the global myocardial work of left ventricle in two types of hypertrophy using noninvasive myocardial work index (NMWI). Methods: Conventional echocardiography was performed in 107 subjects with preserved left ventricular ejection fraction (LVEF≥50%), who comprised patients with HCM (n = 40), H-LVH (n = 35), and healthy people with normal blood pressure and left ventricular structure (n = 32). Except the conventional echocardiographic parameters, the left ventricular myocardial work parameters based on pressure-strain loops, including global myocardial work index (GWI), global constructive work (GCW), global wasted work (GWW), and global work efficiency (GWE), were evaluated in three groups . Multivariate discriminant analysis and receiver operating characteristic (ROC) curve were used to evaluate the incremental value of NMWI for distinguishing HCM from H-LVH. Results: Compared to the control group, GWI and GCW were significantly lower in HCM patients (P < 0.05), whereas GWI was significantly higher in H-LVH patients. GWW was higher and GWE was significantly decreased in both HCM and H-LVH patients than the control group (P < 0.05). Multivariate discriminant analysis and ROC curve revealed that the inter-ventricular septum thickness (IVST)/left ventricular posterior wall thickness (LVPWT) and GCW were each able to distinguish HCM from H-LVH, the combination of IVST/LVPWT and GCW discriminated HCM and H-LVH with a higher predictive accuracy of 94.7%. Conclusion: NMWI may provide additional information in evaluating the myocardial function in patients with HCM and H-LVH. Myocardial work combined with conventional echocardiography could improve the clinical diagnostic accuracy of distinguishing HCM and H-LVH.